Model Predictive Voltage Control with Optimal Duty Cycle for Three-Phase Grid-Connected Inverter - Shahrouz Ebrahimpanah; Qihong Chen; Liyan Zhang; Misbawu Adam (Journal of Control Science and Engineering)
This paper proposes a model predictive voltage control (MPVC) strategy with duty cycle control for grid-connected three-phase inverters with output LCL filter. The model of the system is used to predict the capacitor filter voltage according to the future output current for each possible switching state at each sampling period. Then the cost function for each prediction is determined and the switching state is selected. In the proposed method, two voltage vectors are applied during one sampling interval to achieve better steady-state performance. Finally, the optimal duration of the nonzero voltage vector is defined based on the duty cycle optimization, which is vital to the control system. The proposed strategy offers a better reference tracking error with less THD in linear and nonlinear load situations. The effectiveness of the proposed method has been verified by MATLAB/Simulink and experimental results exhibit a better steady-state performance with less sampling frequency.